Solve for all values of \( x \) by factoring \[ x^{2}+x-12=x+4 \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation \( x^{2} + x - 12 = x + 4 \), first, we can simplify it by moving all terms to one side: \[ x^{2} + x - 12 - x - 4 = 0 \] This simplifies to: \[ x^{2} - 16 = 0 \] Next, we can factor this expression. Notice that \( x^{2} - 16 \) is a difference of squares, which can be factored as: \[ (x - 4)(x + 4) = 0 \] Now, we set each factor equal to zero to solve for \( x \): 1. \( x - 4 = 0 \) ⟹ \( x = 4 \) 2. \( x + 4 = 0 \) ⟹ \( x = -4 \) So, the solutions are: \[ \boxed{4 \text{ and } -4} \]